(untitled) (Hekima Review, 2014)
Our elders say that proverbs are the palm oil with which words are eaten; for words are yam and proverbs the palm oil. It is said to be a recipe for digesting talks. It is in this light that we shall be looking at wise sayings of our elders from the Nigerian extraction. I do notintend to interpret these proverbs less I undermine the very nature of this wise sayings of our elders. For it is said, if a person asks for the meaning of a proverb the bride price paid on his mother is a mere waist.